No return address : a memoir of displacement - Vlasopolos, Anca, 1948- (Columbia University Press, 2000)
In recounting her life's journey from Romania to the United States, Vlasopolos writes movingly of the peculiar attributes of displacement in the contemporary world. Vlasopolos renders a loving portrait of her mother, an Auschwitz survivor courageously raising a young girl alone after the death of her husband, a political dissident, and finally, details their years of limbo in Brussels and Paris and settlement in Detroit, Michigan.